2019
DOI: 10.1111/jcmm.14728
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA TNRC6C‐AS1 promotes methylation of STK4 to inhibit thyroid carcinoma cell apoptosis and autophagy via Hippo signalling pathway

Abstract: The role of long non‐coding RNAs (lncRNAs) in thyroid carcinoma (TC), the most frequent endocrine malignancy, has been extensively examined. This study investigated effect of interaction among lncRNA TNRC6C‐AS1, serine/threonine‐protein kinase 4 (STK4) and Hippo signalling pathway on TC. Initially, lncRNA TNRC6C‐AS1 expression in TC tissues was detected. To explore roles of lncRNA TNRC6C‐AS1, STK4 and Hippo signalling pathway in TC progression, their expressions were altered. Interaction between lncRNA TNRC6C‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In recent years, the Hippo signaling pathway has been found to be closely associated with tumor progression. For example, TNRC6C‐AS1 expedites the methylation of STK4 to inhibit thyroid carcinoma cell apoptosis through the Hippo signaling pathway 17 . HOX transcript antisense RNA directly binds to SAV1 and activates the Hippo pathway in renal cell carcinoma 18 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the Hippo signaling pathway has been found to be closely associated with tumor progression. For example, TNRC6C‐AS1 expedites the methylation of STK4 to inhibit thyroid carcinoma cell apoptosis through the Hippo signaling pathway 17 . HOX transcript antisense RNA directly binds to SAV1 and activates the Hippo pathway in renal cell carcinoma 18 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the four overlapping target genes of miR-7977 (CCL22, STK4, HSPA1B, and ACTR2) in all three databases were reported to have a key role in cancer formation and metastasis. Studies have shown that these genes are involved in the growth, invasion, and metastasis of a variety of tumors, and that they play a key role in tumorrelated molecular mechanisms (30)(31)(32)(33). Furthermore, abnormal signaling pathways also play crucial roles in the development of cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary studies also showed that knockdown of UCA1 had an inhibitory effect on AML cell proliferation in vitro and tumourigenesis in vivo. LncRNAs also function as crucial regulators of autophagy . Existing evidence suggests that UCA1 can regulate autophagy in several diseases, such as ischaemia‐reperfusion injury, colorectal cancer, and bladder cancer .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs also function as crucial regulators of autophagy. 18,19 Existing evidence suggests that UCA1 can regulate autophagy in several diseases, such as ischaemia-reperfusion injury, 20 colorectal cancer, 21 and bladder cancer. 22 Nevertheless, the regulatory role and detailed mechanism of UCA1 in autophagy in AML remain unclear.…”
mentioning
confidence: 99%